Biosensors with Metal Ion–Phosphate Chelation Interaction for Molecular Recognition - Xiaohua Ma; Yuanqiang Hao; Xiaoxiao Dong; Ning Xia (Molecules, 2023)
Biosensors show promising prospects in the assays of various targets due to their advantages of high sensitivity, good selectivity and rapid response. Molecular recognition is a key event of biosensors, which usually involves the interaction of antigen–antibody, aptamer–target, lectin–sugar, boronic acid–diol, metal chelation and DNA hybridization. Metal ions or complexes can specifically recognize phosphate groups in peptides or proteins, obviating the use of biorecognition elements. In this review, we summarized the design and applications of biosensors with metal ion–phosphate chelation interaction for molecular recognition. The sensing techniques include electrochemistry, fluorescence, colorimetry and so on.